Geronimo Stilton #40 : The karate mouse - Stilton, Geronimo (Scholastic, 2010)
Geronimo Stilton gets caught up in the World Karate Championships, thanks to the efforts of Bruce Hyena and Piccolo Tao, Bruce's super-sporty cousin. Geronimo only has a week to become real champion material! Will Geronimo manage to overcome his fears in order to win the competition?